A New Understanding of Dorsal Dysraphism with Lipoma (Lipomyeloschisis): Radiologic Evaluation and Surgical Correction - Naidich, Thomas P.; McLone, David G.; Mutluer, Saffet (American Journal of Neuroradiology, 1983)
The spinal anomaly designated dorsal dysraphism with lipoma (lipomyeloschisis) consists of skin-covered, focal spina bifida; focal partial clefting of the dorsal half of the spinal cord; continuity of the dorsal cleft with the central canal of the cord above (and occasionally below) the cleft; deficiency of the dura underlying the spina bifida; deep extension of subcutaneous lipoma through the spina bifida and the dural deficiency to insert directly into the cleft on the dorsal half of the cord; variable cephalic extension of lipoma into the contiguous central canal of the cord; and variable ballooning of the subarachnoid space to form an associated meningocele. The variable individual expressions of the anomaly are best understood by reference to their archetypal concept. Careful analysis of radiographic and surgical findings in human lipomyeloschisis and correlation with an animal model of lipomyeloschisis indicate that plain spine radiographs and high-resolution metrizamide computed tomographic myelography successfully delineate the precise anatomic derangements associated with lipomyeloschisis and provide the proper basis for planning surgical therapy of this condition.